Effectiveness of two-dimensional CFD simulations for Darrieus VAWTs: a combined numerical and experimental assessment. (15th March 2017) - Bianchini, Alessandro; Balduzzi, Francesco; Bachant, Peter; Ferrara, Giovanni; Ferrari, Lorenzo
Graphical abstract: Highlights: 2D CFD simulations compared to experimental tow-tank data on the RVAT test model. The use of CFD with open-field-like boundaries is suggested. A reliable estimation of the turbine performance and the wake structure is obtained. The transitional turbulence model is recommended for low TSRs and/or small rotors. The wake analysis identified the main vortical structures generated by the blades. Abstract: Thanks to the continuous improvement of calculation resources, computational fluid dynamics (CFD) is expected to provide in the next few years a cost-effective and accurate tool to improve the understanding of the unsteady aerodynamics of Darrieus wind turbines. This rotor type is in fact increasingly welcome by the wind energy community, especially in case of small size applications and/or non-conventional installation sites. In the present study, unique tow tank experimental data on the performance curve and the near-wake structure of a Darrieus rotor were used as a benchmark to validate the effectiveness of different CFD approaches. In particular, a dedicated analysis is provided to assess the suitability, the effectiveness and the future prospects of simplified two-dimensional (2D) simulations. The correct definition of the computational domain, the selection of the turbulence models and the correction of simulated data for the parasitic torque components are discussed in this study. Results clearly show that, (only) if properly set, two-dimensional CFD simulations are able to provide - with a reasonable computational cost - an accurate estimation of the turbine performance and also quite reliably describe the attended flow-field around the rotor and its wake.